REVIEWING THE DEVELOPMENT OF INTELLIGENCE IN CREATING A PROSPEROUS COMMUNITY - Alfin Reza Syahputra (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2023)
Welfare is a measure of a society that is already in a state of prosperity. Welfare can be measured by health, economic condition, happiness and quality of life of the people. The role of intelligence in realizing the welfare of society is quite important. Because in carrying out the process of developing a community, objective data is needed that is valid to be used as material for problem analysis.Through a descriptive approach, this research examines phenomena through the discovery and description of data in a narrative manner. The data collection technique used is library research, namely collecting books, journals, and other relevant research and then reviewing them.To realize prosperity for the community, four elements are needed to conceptualize it. (1) the existence of information or knowledge; (2) the existence of an analytical strategy; (3) the existence of potential threats; and (4) the existence of safeguards against national interests and security. These four elements are owned by Intelligence and become the basic concept. The role of intelligence agencies in creating a prosperous society has a central position. So it can be said that the field of intelligence has a very large and much needed role in realizing a prosperous society.